Berberine Attenuates Macrophages Infiltration in Intracranial Aneurysms Potentially Through FAK/Grp78/UPR Axis - Quan, Kai; Li, Sichen; Wang, Dongdong; Shi, Yuan; Yang, Zixiao; Song, Jianping; Tian, Yanlong; Liu, Yingjun; Fan, Zhiyuan; Zhu, Wei (Frontiers in Pharmacology, 2018)
Background: Inflammatory cells, such as macrophages, play key roles in the pathogenesis of intracranial aneurysms (IAs). Berberine (BBR), an active component of a Chinese herb Coptis chinensis French, has been shown to have anti-inflammatory properties through suppressing macrophage migration in various inflammation animal model. The goal of this study was to examine BBR’s effect on inflammation and IAs formation in a rodent aneurysm model. Methods and Results: Human aneurysm tissues were collected by microsurgical clipping and immunostained for phospho-Focal adhesion kinase (FAK) and CD68+ macrophages. A rodent aneurysm model was induced in 5-week-old male Sprague Dawley (SD) rats by intracranial surgery, then these rats were orally administrated 200 mg/kg/day BBR for 35 days. Immunostaining data showed that BBR inhibited CD68+ macrophages accumulation in IAs tissues and suppressed FAK phosphorylation. In lipopolysaccharide (LPS)-stimulated RAW264.7 cells, BBR treatment remarkably attenuated macrophages infiltration, suppressed the expression of matrix metalloproteinases (MMPs), and reduced proinflammatory cytokine secretion, including MCP-1, interleukin 1β (IL-1β), interleukin 6 (IL-6) and tumor necrosis factor-a (TNF-α). Mechanistically, BBR downregulated FAK/Grp78/Unfolded Protein Response (UPR) signaling pathway in RAW264.7 cells. Conclusions: BBR prevents IAs formation potentially through inhibiting FAK phosphorylation and inactivating UPR pathway in macrophages, which causes less macrophage infiltration and reduced proinflammatory cytokine release.